PENGARUH KONSEP DIRI DAN KEPUASAN KERJA DENGAN KINERJA GURU MADRASAH ALIYAH DI KECAMATAN ANJIR PASAR KABUPATEN BARITO KUALA - Mohammad Manan,; Khuzaini, Khuzaini; Husnul Madihah, (Journal of Innovation Research and Knowledge, 2023)
The spearhead in efforts to improve the quality of education is educators, namely Teachers. In an effort to improve the quality of national education, the government through the Ministry of National Education is still trying to make various changes and renewal of the professional education system, namely with efforts that have been and are being made related to teacher factors, especially regarding teacher performance. This quantitative research aims to find out how much the influence of the self-concept and job satisfaction on the performance teachers of Madrasah Aliyah in Anjir Pasar Subdistrict Barito Kuala Regency. The purpose of this study was to find out and describe: (1) The influence between self-concept and teacher performance of Madrasah Aliyah in Anjir Pasar Subdistrict Barito Kuala Regency, (2) The influence between job satisfaction and teacher performance in Madrasah Aliyah in Anjir Pasar Subdistrict Barito Kuala Regency and (3) The influence between self-concept and job satisfaction together with the teacher's performance Madrasah Aliyah in Anjir Pasar Subdistrict Barito Kuala Regency. Data collection methods with questionnaires, documentation, observation, and interviews. The data was obtained from a sample of Madrasah Aliyah Fathussalam teachers, Madrasah Aliyah Ibtidaussalam and Madrasah Aliyah Asasussalam. By using regression analysis as data analysis. Based on the results of the study found that: 1) There is an influence of the self-concept on teacher performance by 12,1% with a regression line equation Y = 19,428 + 0,727X1. 2) There is an influence of job satisfaction on teacher performance, which is 26,2% with a regression line equation Y = 7,113 + 0,890X2. 3) There is an influence of the self-concept and job satisfaction on teacher performance that is equal to 26,4% with the regression line equation Y = -0,636 + 0,125X1 + 0,827X2. Thus, efforts to improve performance in Madrasah Aliyah teachers in Anjir Pasar Subdistrict Barito Kuala Regency can be increased again by increasing the factors that affect performance. These include self-concept and job satisfaction. Where when these two factors increase, teacher performance will also increase.